Customs Intelligence Surveillance and Analysis Tools in Anticipation of Smuggling Threats - Tanjung, Rully Eko Setiawan; Rofii, Muhammad Syaroni; Anriani, Stepi (International Journal Labs, 2023)
Customs intelligence activities carried out by the intelligence unit are carried out in the context of early detection of violations in the field of customs and excise. One of the threats facing customs is the threat of smuggling which can be detrimental to the state and society. the purpose of this study is to determine customs intelligence supervision and the use of external data service applications that become customs intelligence analysis tools. This study uses a qualitative method with a descriptive approach. The results of the first study show that the surveillance activities that have been carried out by customs intelligence are in accordance with the intelligence cycle which includes collection, assessment, analysis, distribution, evaluation and updating of data and/or information. Customs violations related to export-import activities can be categorized as smuggling crimes. The results of the second study show that customs intelligence analysts use external data service applications such as: Global Trade Atlas (GTA), Automatic Identification System (AIS), Marine Traffic, Sea Web, Panjiva, Questnet, Intelligence Media Analytics (IMA), and Intelligence Socio. Analytics (ISA) for targeting, profiling, and document research. Supervision by customs intelligence using the help of external data service applications is utilized by intelligence analysts as an analytical tool in order to anticipate the threat of smuggling.